2014
DOI: 10.18632/oncotarget.2820
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor alpha drives proliferation in PTEN-deficient prostate carcinoma by stimulating survival signaling, MYC expression and altering glucose sensitivity

Abstract: While high doses of estrogen, in combination with androgens, can initiate prostate cancer (PCa) via activation of the estrogen receptor α (ERα), the role of ERα in PCa cells within established tumors is largely unknown. Here we show that expression of ERα is increased in high grade human PCa. Similarly, ERα is elevated in mouse models of aggressive PCa driven by MYC overexpression or deletion of PTEN. Within the prostate of PTEN-deficient mice, there is a progressive pattern of ERα expression: low in benign gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 57 publications
3
50
1
2
Order By: Relevance
“…The most significant ERα gene expression, at mRNA and protein levels, was observed in hormone refractory tumours and metastatic lesions, including lymph node and bone metastases (Bonkhoff et al 1999). Furic and coworkers (Takizawa et al 2015) selected a cohort of tumours of Gleason grade 6 and 9 to ensure that both low-and high-grade tumours were represented; they found that ERα was expressed in 48% of Gleason score 9 specimens, but no ERα was observed in the Gleason score 6 tumours, thus confirming the earlier findings by Bonkhoff and coworkers. Another recent study reported that 15% of locally invasive tumours, spanning Gleason score 6-10, expressed ERα and that it was significantly associated with biochemical recurrence, decreased progression-free survival and poor overall survival (Takizawa et al 2015).…”
Section: Oestrogen Receptors (Erα or Nr3a1 And Erβ Or Nr3a2)supporting
confidence: 67%
See 2 more Smart Citations
“…The most significant ERα gene expression, at mRNA and protein levels, was observed in hormone refractory tumours and metastatic lesions, including lymph node and bone metastases (Bonkhoff et al 1999). Furic and coworkers (Takizawa et al 2015) selected a cohort of tumours of Gleason grade 6 and 9 to ensure that both low-and high-grade tumours were represented; they found that ERα was expressed in 48% of Gleason score 9 specimens, but no ERα was observed in the Gleason score 6 tumours, thus confirming the earlier findings by Bonkhoff and coworkers. Another recent study reported that 15% of locally invasive tumours, spanning Gleason score 6-10, expressed ERα and that it was significantly associated with biochemical recurrence, decreased progression-free survival and poor overall survival (Takizawa et al 2015).…”
Section: Oestrogen Receptors (Erα or Nr3a1 And Erβ Or Nr3a2)supporting
confidence: 67%
“…Furic and coworkers (Takizawa et al 2015) selected a cohort of tumours of Gleason grade 6 and 9 to ensure that both low-and high-grade tumours were represented; they found that ERα was expressed in 48% of Gleason score 9 specimens, but no ERα was observed in the Gleason score 6 tumours, thus confirming the earlier findings by Bonkhoff and coworkers. Another recent study reported that 15% of locally invasive tumours, spanning Gleason score 6-10, expressed ERα and that it was significantly associated with biochemical recurrence, decreased progression-free survival and poor overall survival (Takizawa et al 2015). A further study has reported that the expression of ERα and aromatase (CYP19) with the R264C polymorphism, a missense SNP located on the CYP19A1 locus, has been shown to result in shorter progression-free survival and an increased risk of developing CRPC in a study of 115 men treated with docetaxel.…”
Section: Oestrogen Receptors (Erα or Nr3a1 And Erβ Or Nr3a2)supporting
confidence: 67%
See 1 more Smart Citation
“…This further demonstrates that ERα regulates cell proliferation through PI3K and MAPK signalling (Takizawa et al 2015).…”
Section: :6mentioning
confidence: 62%
“…Hormone receptor rapid actions and more recently receptor cross talk with other nuclear receptors (i.e., actions that require phosphorylation events) remain hot topics for HOCA content (i.e., estrogen and progesterone or androgen receptor cross talk in breast cancer). Participation of multiple steroid hormone receptors in the same signaling and transcriptional complexes [1,2] is likely a paradigm for many hormone-influenced cancers, such as prostate cancer (where ER-alpha may drive proliferation of advanced disease) [3] and even lung cancer, where progesterone receptor (PR) expression predicts poor outcome, while mineralocorticoid receptor (MR) expression appears to be protective [4].…”
mentioning
confidence: 99%